A Land Lease-Related Document from the Agoranomic Dossier of Daippos. Issue 1 (1st January 2020) - Kotyl, Marcin
Abstract : This paper offers an edition and discussion of a Greek papyrus fragment (P.B.U.G. inv. 122A) dated to the first half of the second century BCE. The document was originally most likely a private six-witness contract which was subsequently validated and registered in the local notary office. It is also argued that the text belongs to the dossier of Daippos, the representative of agoranomos Agathokles, which is the earliest known evidence for the presence and activity of agoranomoi and their agents at that time.